The Influence of Perceived Organizational Support on Employee Well-Being Mediated by Employee Engagement of PT. BPR Bali Dananiaga Employees - Candradewi, I Gusti Agung Istri; Adnyani, I Gusti Ayu Dewi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Employee well-being is a feeling of being appreciated by the company for their contribution which can increase employee dedication and performance. This study is to examine how employee engagement mediates the impact of perceived organizational support on employee well-being. 53 employees participated in the study, which was carried out at PT. BPR Bali Dananiaga using the census method. Data was gathered by means of surveys and interviews. Path analysis using SPSS version 25.0 was the data analysis method employed. The study's findings suggest that employee well-being is positively and significantly impacted by perceived organizational support. Employee well-being is positively and significantly impacted by employee engagement. Employee engagement is positively and significantly impacted by perceived organizational support. The relationship between perceived organizational support and employee well-being is somewhat mediated by employee engagement. This study strengthens Social Exchange Theory and can be an evaluation material for PT. BPR Bali Dananiaga in overcoming employee well-being problems.